A Method for Assessing the Reliability of Heart Rates obtained from Ambulatory ECG - Orphanidou, C; Bonnici, T; Vallance, D; Darrell, A; Charlton, P; Tarassenko, L (2012)
In this paper we present a method of assessing the reliability of heart rates (HRs) obtained from ambulatory ECGs. Our method assigns a Reliability Index (RI) to ECG segments based on a set of physiologically relevant rules prior to using a template matching approach. We validated the algorithm on 1500 manually annotated samples of ECG taken from two different studies and using three different sensors at different sampling rates. The sensitivity of our method was 98% and the specificity was 94%. Our method matched or was more conservative than the human annotations in 99.4% of the samples, making it a promising tool for inclusion in next-generation wearable sensors. © 2012 IEEE.